Non-HDL Cholesterol and LDL Cholesterol as Main Risk Factors for Coronary Heart Disease: Meta-Analysis - Ravell Hansen Untono; Jusak Nugraha; I. Gde Rurus Suryawan; Andrianto Andrianto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Coronary heart disease is a highly frequent illness in both developed and developing nations. Non-HDL cholesterol (n-HDL-c) and LDL cholesterol (LDL-c) stages are biomarkers that doctors frequently utilize to assess the risk of Coronary Heart Disease (CHD). This study was a systematic review and meta-analysis to assess the association between n-HDL-c and LDL-c as major risk factors for CHD. Cochrane, PubMed, and Science Direct searches were conducted using the keywords